A cross sectional study on knowledge, attitude, and practice of road safety measures among medical students at GIMS-Kalaburagi, Kalyana, Karnataka - Dhadave, Meenakshi M.; V. K., Manjunatha; Kumar , G. Ajay (International Journal Of Community Medicine And Public Health, 2023)
Background: According to the World Health Organization (WHO), an accident is defined as an “unpremeditated event resulting in recognizable damage”. The eighth leading cause of death in the world. Most common among children and young ages. Being the young generation in the community, medical students will be able to communicate better regarding precautions related to road safety measures which helps to prevent RTA hence current study was taken. Objectives were to determine the sociodemographic profile of undergraduate medical students at GIMS Kalaburagi. To find the knowledge, attitude, and practice towards road safety measures among medical students. Methods: Undergraduate medical students of GIMS Kalaburagi were selected as study participants. By using convenience sampling, a semi-structured, pretested questionnaire in the form of Google forms was circulated among all medical students out of which 405 responded. Results: A total of 405 students were interviewed, among them 63.2% were males,32.1% majority belonged to phase-3 part-1 95.8% of students had 2-wheeler vehicles whereas only 40% were present with a permanent license. Knowledge about traffic signal and road safety measures were 90.4% and 85.7% respectively. Only 10.6% had a good attitude related to no use of horns in no horn zone areas. The majority 84.2% use PUC-certified vehicles whereas 83.7% always use indicators while taking turns and 77.5% always the use rear mirror while driving. Conclusions: Road traffic accidents are avoidable by proper sense of road safety measures like wearing a helmet, wearing a seatbelt, following all traffic signal rules, avoiding drink and driving which should be encouraged, and also providing IEC and awareness programs among medical students and common people.